Asuhan Keperawatan Keluarga Tn. D Pada Ny. W Dengan Sistem Kardiovaskuler: Hipertensi Di Desa Kutayu RT 04 RW 01 Kecamatan Tonjong Kabupaten Brebes - Khofifah Khofifah; Ahmad Zakiudin; Anna Maulina L (Jurnal Medika Nusantara, 2023)
Based on data from the Nabire District Health Service, case findings in 2009 with the number of sufferers. High blood pressure occurs when blood pressure is too high. A person's blood pressure includes systolic and diastolic blood pressure. Systolic blood pressure is the blood pressure when the heart beats. Diastolic blood pressure is blood pressure when the heart is at rest. Normal blood pressure is 140/90 mmHg (WHO, 2020). In general, hypertension is measured twice with an interval of five minutes under adequate rest. Systolic blood pressure increased by more than 140 mmHg and diastolic blood pressure increased by more than 90 mmHg (Rodrigo Garcia Motta et al., 2021).